Formation of Thin, Isoporous Block Copolymer Membranes by an Upscalable Profile Roller Coating Process—A Promising Way to Save Block Copolymer - Thomas Bucher; Volkan Filiz; Clarissa Abetz; Volker Abetz (Membranes, 2018)
In this work we present a method to manufacture flat sheet membranes with a thin isoporous block copolymer (BCP) layer (thickness <3 µm) by profile roller coating (breadth: 30 cm) on top of a porous support membrane. Highly diluted BCP-solutions were used for this coating process. While we cast membranes with dimensions of 30 cm × 50 cm in this work, the procedure can easily be extended to endless dimensions in this roll to roll (R2R) process. The method offers the possibility to save >95% of BCP raw material compared to common doctor blade casting, by strongly decreasing the layer thickness to below 3 µm in combination with a highly open substructure. Additionally, we report a straightforward method to investigate the influence of the solvent evaporation time between coating and precipitation (phase inversion) on the membrane morphology using one sample only, which also ensures that all other influencing parameters remain constant.